A wearable fiber-optic sensor for monitoring human elbow and wrist joint motion. (3rd April 2021) - Li, Min; He, Bo; Zhao, Xingang; Xie, Jun; Yao, Wei; Xu, Guanghua
Abstract : This article describes a wearable sensor for monitoring the motion of human elbow and wrist joints. The sensor converts the joint motion angle into a displacement, which is monitored using a fiber-optic sensor based on reflective light intensity modulation. A mathematical model is established, and the potential influencing factors of the sensor are investigated. Two prototypes for elbow and wrist joint angle monitoring are fabricated and validated. The experimental results indicate that the proposed sensor has a measurement range of 0–60° (0–120°), with a resolution of 0.338° (3.6°) for monitoring the wrist joint palm flexion (elbow joint flexion). The proposed sensor has the potential to be used for rehabilitation purposes and monitoring of joint angles while performing reaching tasks, which are the most common upper-limb gestures. GRAPHICAL ABSTRACT: